Effect of calcination temperatures on the Ba(Zn1/3Ta2/3)O3 phase formation - Hidayani, Jaafar; Mohd Fadhil, Ain; Zainal Arifin, Ahmad (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.